Ritual Dan Tradisi Sebagai Identitas Budaya: Kajian Antropologi Di Masyarakat Indonesia - Rosdahliani (CV. SINAR HOWUHOWU, 2025)
This article examines the fundamental role of rituals and traditions as performative mechanisms in the construction and affirmation of cultural identity within Indonesia's pluralistic society. Through a qualitative approach with an ethnographic design, this research focuses its analysis on two contrasting case studies: the communal death ritual of Ngaben in Bali and the familial life-cycle tradition of Tedak Siten in Java. The findings indicate that despite their differences in scale and context, both practices function as vital arenas where values, cosmology, and social bonds are articulated and reinforced. Ngaben constructs a collective identity through public participation and communal solidarity, while Tedak Siten instills the foundation of cultural identity at the individual and family level from an early age. This study concludes that ritual is not merely a static heritage but a dynamic and adaptive